A guide to the responsories of the Ambrosian Office. Issue 1 (15th March 2016) - BAILEY, TERENCE
ABSTRACT: A guide, with historical observations, that distinguishes the kinds of responsories employed in the Ambrosian liturgy, describes their liturgical functions and performance practice, determines the size of the various repertories, and discusses the textual and musical characteristics of the types.